Eksplorasi dampak kesepian pada pasien di intensive care unit (ICU): Tinjauan sistematik - Setiawan, Deris Riandi; Kosasih, Cecep Eli; Mirwanti, Ristina (Holistik Jurnal Kesehatan, 2025)
Background: Loneliness is a significant emotional challenge for Intensive Care Unit (ICU) patients that is often exacerbated by physical and social isolation due to visiting restrictions. This condition can impact the mental and physical well-being of patients, making it important for healthcare providers to develop a deep understanding of loneliness in ICU patients. Purpose: To explore the impact of loneliness in intensive care unit (ICU) patients. Method: The narrative review research design was derived from quantitative and qualitative studies using the Reporting for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The article selection process used questions with a population, concept, and context (PCC) approach including; P: Intensive Care Unit (ICU) patients; C: impact of loneliness; and C: ICU patient outcomes. Inclusion criteria for this narrative review were accessible full-text articles, published in English, articles with both qualitative and quantitative designs, and published within a 5-year period (2019-2024). A search was conducted on three major databases (CINAHL, PubMed, and Scopus) yielding a total of 52 articles and after an elimination process, 5 articles were obtained for review. Results: Loneliness in ICU patients has a significant impact on emotional, physical, and social health, including decreased mental health, quality of life, and increased risk of death. Conclusion: This review emphasizes the importance of a holistic approach in ICU care that includes physical, psychological, and social aspects of patients. Optimal psychosocial support is expected to reduce the negative impact of loneliness and improve the quality of life of ICU patients. Suggestion: Health workers can improve a more holistic approach by paying attention to psychological, social, and emotional support. This is expected to reduce feelings of loneliness experienced by patients and ultimately accelerate the recovery process and improve the quality of life of patients in the ICU environment.   Keywords: Intensive Care Unit (ICU); Loneliness; Patients.   Pendahuluan: Kesepian merupakan tantangan emosional signifikan bagi pasien di Intensive Care Unit (ICU) yang sering diperburuk oleh isolasi fisik dan sosial akibat kebijakan pembatasan kunjungan. Kondisi ini dapat memengaruhi kesejahteraan mental dan fisik pasien, sehingga penting bagi tenaga medis untuk mengembangkan pemahaman mendalam mengenai rasa kesepian pada pasien ICU. Tujuan: Untuk mengeksplorasi dampak kesepian pada pasien intensive care unit (ICU). Metode: Desain penelitian tinjauan naratif didapat dari penelitian studi kuantitatif dan kualitatif menggunakan panduan Reporting for Systematic Reviews and Meta-Analysis (PRISMA). Proses pemilihan artikel menggunakan pertanyaan dengan pendekatan population, concept, dan context (PCC) meliputi; P: Pasien di Intensive Care Unit (ICU); C: dampak loneliness; dan C: outcomes pasien di ICU. Kriteria inklusi pada tinjauan naratif ini adalah artikel full text dapat diakses, dipublikasikan dalam Bahasa Inggris, artikel dengan desain kualitatif dan kuantitatif serta dipublikasikan dalam rentang 5 tahun (2019-2024). Pencarian dilakukan pada tiga database utama (CINAHL, PubMed, dan Scopus) yang menghasilkan total 52 artikel dan setelah proses eliminasi, didapatkan 5 artikel untuk telaah. Hasil: Perasaan kesepian pada pasien ICU berdampak signifikan pada kesehatan emosional, fisik, dan sosial, yang mencakup penurunan kesehatan mental, kualitas hidup, dan peningkatan risiko mortalitas. Simpulan: Tinjauan ini menegaskan pentingnya pendekatan holistik dalam perawatan ICU yang mencakup aspek fisik, psikologis, dan sosial pasien. Dukungan psikososial yang optimal diharapkan dapat mengurangi dampak negatif kesepian dan meningkatkan kualitas hidup pasien ICU. Saran: Tenaga kesehatan dapat meningkatkan pendekatan yang lebih holistik dengan memperhatikan dukungan psikologis, sosial, dan emosional. Hal ini diharapkan dapat mengurangi perasaan kesepian yang dialami pasien dan pada akhirnya mempercepat proses pemulihan dan meningkatkan kualitas hidup pasien di lingkungan ICU.   Kata Kunci: Intensive Care Unit (ICU); Kesepian; Pasien.